2016
DOI: 10.1016/j.ijbiomac.2016.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rice starch-ι-carrageenan biodegradable edible film. Effect of stearic acid on the film properties

Abstract: The main aim of this study was to develop rice starch (RS), ι-carrageenan (ι-car) based film. Different formulations of RS (1-4%, w/w), ι-car (0.5-2%, w/w) was blended with stearic acid (SA; 0.3-0.9%, w/w) and glycerol (1%, w/w) as a plasticizer. The effect of film ingredients on the thickness, water vapour permeability (WVP), film solubility (FS), moisture content (MC), colour, film opacity (FO), tensile strength (TS), elongation-at-break (EAB) of film was examined. Interactions and miscibility of partaking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
108
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 42 publications
9
108
2
2
Order By: Relevance
“…Increases in MS concentration led to decreases in the films’ EB. These results were in agreement with those of Thakur et al, who reported a decrease in the EB of rice starch films with decreasing the ɩ‐carrageenan concentration (Thakur et al, ). According to Table , neat MS film showed the lowest EB (6.08%).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Increases in MS concentration led to decreases in the films’ EB. These results were in agreement with those of Thakur et al, who reported a decrease in the EB of rice starch films with decreasing the ɩ‐carrageenan concentration (Thakur et al, ). According to Table , neat MS film showed the lowest EB (6.08%).…”
Section: Resultssupporting
confidence: 93%
“…Generally, the incorporation of PG with MS could form more hydrogen bonds between the two polymers and reinforce the network of composite films; this has been reported in previous studies (Martins et al, ; Sukhija et al, ; Thakur et al, ).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations